Dispersal and group formation dynamics in a rare and endangered temperate forest bat (Nyctalus lasiopterus, Chiroptera: Vespertilionidae). Issue 22 (20th October 2016) - Santos, João D.; Meyer, Christoph F. J.; Ibáñez, Carlos; Popa‐Lisseanu, Ana G.; Juste, Javier
Abstract: For elusive mammals like bats, colonization of new areas and colony formation are poorly understood, as is their relationship with the genetic structure of populations. Understanding dispersal and group formation behaviors is critical not only for a better comprehension of mammalian social dynamics, but also for guiding conservation efforts of rare and endangered species. Using nuclear and mitochondrial markers, we studied patterns of genetic diversity and differentiation among and within breeding colonies of giant noctule bats ( Nyctalus lasiopterus ), their relation to a new colony still in formation, and the impact of this ongoing process on the regionwide genetic makeup. Nuclear differentiation among colonies was relatively low and mostly nonsignificant. Mitochondrial variation followed this pattern, contrasting with findings for other temperate bat species. Our results suggest that this may indicate a recent population expansion. On average, female giant noctules were not more closely related to other colony members than to foreign individuals. This was also true for members of the newly forming colony and those of another, older group sampled shortly after its formation, suggesting that contrary to findings for other temperate bats, giant noctule colonies are not founded by relatives. However, mother–daughter pairs were found in the same populations more often than expected under random dispersal. Given this indication of philopatry, the lack of mitochondrial differentiation among most colonies in the region is probably due to the combination of a recent population expansion and group formation events. Abstract : Genetic methods can be an important tool for deciphering the complex social habits of small, vagile species. We studied the genetic structure and distribution of female kin of a rare and endangered temperate bat, Nyctalus lasiopterus, across four maternity colonies in Andalusia, Spain. The crash and recolonization of one of these sites provided us with the rare opportunity to study colony formation in a social species from a genetic standpoint. Genetic structure was weak or absent across colonies, even at the mitochondrial level. However, the distribution of close kin suggested strong philopatry, and average parwise‐relatedness among colonizers was high. Photo: Jens Rydell